Results of Continuous Improvement Adopted in Selected Manufacturing Companies of Punjab - Singh , Jagdeep; Singh , Harwinder (Gyan Management Journal, 2012)
In today’s highly competitive and rapidly changing environment, manufacturing scenario has undergone a rapid change in the last two decades, more so in the last few years. The manufacturing units are continuously trying to update themselves by developing modern improvement techniques like Total Productive Maintenance, Total Quality Management and Continuous Improvement. Continuous improvement CI) activities are recognized as a way of contributing to the productivity and efficiency within the manufacturing setting through small incremental changes. The present study attempts to evaluate the performance of Continuous Improvement approach in manufacturing industry of Punjab by identifying the important benefits achieved after successful implementation of this technique. Result indicated that Continuous Improvement approach is highly helpful in gaining profit, reducing material and operator movement, reducing operator mistakes, reducing cost of consumables, maintaining health and safety standards, and providing customer satisfaction by providing at a time delivery of a product.